Detection of modiolar proximity through bipolar impedance measurements. (24th August 2016) - Pile, Jason; Sweeney, Alex D.; Kumar, Shaun; Simaan, Nabil; Wanna, George B.
Abstract : Objectives: To test the hypothesis that bipolar electrical impedance measurements in perimodiolar cochlear implants (CIs) may be used to differentiate between perimodiolar insertion technique favoring proximity to the modiolus or lateral wall. Study Design and Methods: Bipolar impedances are a measure of electrical resistance between pairs of electrode contacts in a CI. Stimulation is through biphasic pulses at fixed frequency. Impedance measurements were made in real time through sequential sampling of electrode pairs. Perimodiolar electrodes were inserted in temporal bones using one of two techniques: 1) In the standard insertion technique (SIT), the electrode array slides along the lateral wall during insertion. 2) In the Advance Off Stylet (Cochlear Ltd. Sydney) technique (AOS), the electrode maintains modiolar contact throughout the insertion process. A set of 22 insertions were performed in temporal bone specimens using perimodiolar electrode arrays with both AOS and SIT. Buffered saline was used as a substitute for natural perilymph based on similar electrical conductivity properties. Impedance with and without stylet removal were recorded with a 30‐second sampling window at final insertion depth. Results: There is a significant difference in bipolar impedance measures between AOS and SIT, with impedances rising in measurements with stylet removal. Evaluation was based on two‐sided analysis of variance considering technique and electrode with P < 0.025. Conclusion: Bipolar electrical impedance can be used to detect relative motion toward the modiolus inside the cochlea. This detection method has the potential to optimize intraoperative placement of perimodiolar electrode arrays during implantation. We anticipate that this will result in lower excitation thresholds and improved hearing outcome. Level of Evidence: NA. Laryngoscope, 127:1413–1419, 2017